Prevalence of low back pain and its risk factors among school teachers - Abdul Samad, Nurul Izzah; Abdullah, Haslinda; Moin, Saidi; Mohd Tamrin, Shamsul Bahri; Hashim, Zailina (Science Publications, 2010)
The objective of this study was to determine the prevalence of low back pain and the associated risk factors among primary school teachers in the Klang Valley, Malaysia. Approach: A cross sectional study was conducted in nine primary schools in the Klang Valley. The schools were selected randomly from a list obtained from the Ministry of Education. Two hundred and seventy two respondents who fulfilled the study criteria volunteered to participate in the study. A questionnaire was used to determine the demographic and occupational information. Information on low back pain was assessed using a Nordic Questionnaire, while the General Health Questionnaire was used to determine the mental health status. Results: The prevalence of low back pain was 40.4% among respondents. Lifting load (28.0%) was ranked as the main factor which contributed to low back pain, followed by prolonged sitting (25.2%). Poor mental health (OR 1.11, 95% CI 1.06-1.15) was the risk factor to low back pain. Conclusion: The prevalence of low back pain was 40.4% among primary school teachers in Klang Valley. Teachers with poor mental health status had higher risk of developing low back pain.